2022
DOI: 10.3390/su14031573
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Sustainable Fresh Fruit and Vegetable Supply Chains

Abstract: Fresh fruit and vegetables are crucial for human health. Their fibrous structure and high nutritional value are essential for people’s well-being. This study aims to provide a review of the current state of knowledge and practices regarding fresh fruit and vegetable supply chains (FFVSC). The reviewed papers are divided into categories according to their findings, research purposes, tools and messages used. Our objective is to guide both academics and practitioners by pointing out significant streams of resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 119 publications
(116 reference statements)
1
8
0
Order By: Relevance
“…Though a greater decline was seen in transport from Spain (approximately 5%), as an absolute decline in nutrient content, all instances are low. This is likely a consequence of the use of cold supply chains for fresh produce transportation (Tort et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Though a greater decline was seen in transport from Spain (approximately 5%), as an absolute decline in nutrient content, all instances are low. This is likely a consequence of the use of cold supply chains for fresh produce transportation (Tort et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Another study conducted in 2022 explored this research stream and found eight clusters of the field in science mappingvalue chain indicators of fresh fruit and vegetable supply chains, food-related problems/postharvest losses along fresh fruit and vegetable supply chains, roles of parties involved in the fresh fruit and vegetable value chain, review papers, technological trends in fresh fruit and vegetable supply chains, packaging issues of fresh fruit and vegetable supply chains, logistics solutions of fresh fruit and vegetable supply chains, and sustainable fresh fruit and vegetable supply chains (Tort et al, 2022). Although this review was a comprehensive and integrative attempt to review the existing research, due to its product-specific nature, the ecological validity of the paper is limited and there is a need to address this issue with a study that can provide an overall mapping and overview of the field.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study conducted in 2022 explored this research stream and found eight clusters of the field in science mapping – value chain indicators of fresh fruit and vegetable supply chains, food-related problems/postharvest losses along fresh fruit and vegetable supply chains, roles of parties involved in the fresh fruit and vegetable value chain, review papers, technological trends in fresh fruit and vegetable supply chains, packaging issues of fresh fruit and vegetable supply chains, logistics solutions of fresh fruit and vegetable supply chains, and sustainable fresh fruit and vegetable supply chains (Tort et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The sensors detect the fruit maturity loss (Baietto and Wilson, 2015 ) using the “Export Progress” information, and the export progress loss is then estimated. Hence, the industry should stimulate advanced management ideas on strategy simulation and recoup a part of the sensor cost while increasing fruit quality (Tort et al, 2022 ). Using the “maturity” information, a mango ripeness data feed is essential to train a self-supervised deep learning model to predict shelf-life (Nordey et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%